Determinant Factors of Work-Related Complaints - Qoni Mulia Sagita; Yuliani Setyaningsih; Sulistiyani Sulistiyani (International Journal of Public Health Science (IJPHS), 2018)
Home-based workers of Footwear industries in Semarang Regency are all womans. The employment status of home-based workers usually unrecognized or unregulated by the employer or their itermediaries so that they did not paid close attention about HWBs’s working condition. They often work on inadequate working environment such as poor ventilation system, bad lighting, humid working space (damp wall and floor), and also poor layout of furnitures and work equipments. That condition exaberated by lack of HWBs’s knowledge and awareness regarding their health and safety at work. In addition HBWs often with little to none education, work on long extended working hours and working under intensive labor.This research was aimed to determine the relationship between respondent characteristics, medical history, and use of PPE with work-related complaints on home workers of shoe industry in Semarang regency. This was an observational analytic study using cross sectional approach. Population in this study was 80 home workers of shoe industry in Semarang regency. The samples are 66 home workers were taken using stratified random sampling method. Data were analyzed using frequency distribution and Chi-Square test. The results of this study showed that there were some variables that have significant association with work-related complaints (p≤ 0.05) including, length of work, duration of work, personal protective equipment (PPE). While the variables of age, body mass index (BMI), and medical history did not show significant association with work-related complaints (p> 0.05). Multivariate analysis using logistic regression showed the duration of work had the most powerful influence to the work-related complaints. The conclusion of this study was important for home workers to maintain health condition by doing exercise to avoid work-related complaints. Home workers that have long duration of work should increase the use of PPE such as masks and gloves.